Peningkatan Hasil Belajar PAI Peserta Didik Melalui Pembelajaran Berbasis Masalah di SMK Negeri 1 Lintau Buo - Ainul Mardiah (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study aims to improve student learning outcomes in Islamic Religious Education and Ethics through the application of the Problem-Based Learning (PBL) model at SMK Negeri 1 Lintau Buo. This Classroom Action Research was conducted in three cycles, each comprising planning, implementation, observation, and reflection. The results showed a significant increase in students' learning mastery, from 52% in the initial stage (pre-cycle) to 86% in the first cycle and 94% in the second cycle. This improvement was achieved through the implementation of PBL, which involved solving real-world problems, utilizing technology-based learning media, and conducting group discussions. The learning model effectively enhanced students' critical thinking, collaboration, and problem-solving skills.